Multi-walled carbon nanotube-based composite materials as catalyst support for water–gas shift and hydroformylation reactions. Issue 47 (3rd September 2019) - Wolf, Patrick; Logemann, Morten; Schörner, Markus; Keller, Laura; Haumann, Marco; Wessling, Matthias
Abstract : Multi-walled carbon nanotubes (MWCNT) show promising behavior in supported ionic liquid phase (SILP) catalyzed hydroformylation and water–gas shift reactions. Abstract : In times of depleting fossil fuel reserves, optimizing industrial catalytic reactions has become increasingly important. One possibility for optimization is the use of homogenous catalysts, which are advantageous over heterogeneous catalysts because of mild reaction conditions as well as higher selectivity and activity. A new emerging technology, supported ionic liquid phase (SILP), was developed to permanently immobilize homogeneous catalyst complexes for continuous processes. However, these SILP catalysts are unable to form freestanding supports by themselves. This study presents a new method to introduce the SILP system into a support made from multi-walled carbon nanotubes (MWCNT). In a first step, SILP catalysts were prepared for hydroformylation as well as low-temperature water–gas shift (WGS) reactions. These catalysts were integrated into freestanding microtubes formed from MWCNTs, with silica (for hydroformylation) or alumina particles (for WGS) incorporated. In hydroformylation, the activity increased significantly by around 400% when the pure MWCNT material was used as SILP support. An opposite trend was observed for WGS, where pure alumina particles exhibited the highest activity. A significant advantage of the MWCNT composite materials is the possibility to coat them with separation layers, which allows their application in membrane reactors for more efficient processes.